Dietary requirements for leucine, isoleucine and valine (branched‐chain amino acids) by juvenile red drum Sciaenops ocellatus. (1st November 2017) - Castillo, S.; Gatlin, D.M.
Abstract: The objective of this study was to determine the minimum dietary requirements of the branched‐chain amino acids (BCAAs: leucine [Leu], isoleucine [Ile] and valine [Val]) for juvenile red drum, Sciaenops ocellatus . This was accomplished by conducting three independent 49‐day feeding trials with juvenile red drum. Experimental diets were prepared by supplementing a basal diet containing 370 g/kg crude protein from red drum muscle and crystalline amino acids with incremental levels of Leu (9.0, 13.0, 17.0, 21.0, 25.0 and 29.0 g/kg of dry diet), Ile (5.0, 8.0, 11.0, 14.0, 17.0 and 20.0 g/kg of dry diet) and Val (6.8, 8.0, 9.2, 10.4, 11.6, 12.8 and 14.0 g/kg of dry diet). Fish were fed to apparent satiation twice daily in each trial, after which growth performance parameters were calculated and body composition and concentrations of BCAAs in plasma were analysed. Incremental levels of dietary Leu, Ile and Val significantly affected weight gain, feed efficiency and protein retention. Analyses of the weight gain data using a broken‐line regression model estimated the minimum Leu, Ile and Val requirements for maximum growth of juvenile red drum to be 15.7 ± 1.7 g/kg (±95% confidence interval), 11.1 ± 2.3 g/kg and 12.4 ± 0.6 g/kg of dry diet, respectively.